(untitled) (European Journal of Economics, Finance and Business Development, 2024)
It is reviewed recent research on the efficiency of the top carpet manufacturing companies in the world using DEA, which is one of the leading methods for efficiency analysis. Through a systematic review, we investigated research trends in terms of research purposes, specific DEA techniques, input and output factors used for models, etc. Based on the review results, future research directions are suggested. The results of this paper provide valuable information and guidelines for future DEA research on carpet manufacturing industry.